2022
DOI: 10.1155/2022/1458143
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Mechanisms by which Artemisinin and Its Derivatives Induce Ferroptosis in the Treatment of Cancer

Abstract: Artemisinin (ART) is a bioactive molecule derived from the Chinese medicinal plant Artemisia annua (Asteraceae). ART and artemisinin derivatives (ARTs) have been effectively used for antimalaria treatment. The structure of ART is composed of a sesquiterpene lactone, including a peroxide internal bridge that is essential for its activity. In addition to their well-known antimalarial effects, ARTs have been shown recently to resist a wide range of tumors. The antineoplastic mechanisms of ART mainly include cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 143 publications
(197 reference statements)
0
34
0
Order By: Relevance
“…System xc‐/GSH/glutathione peroxidase 4 (GPX4) axis plays a pivotal role in preventing lipid peroxidation induced ferroptosis 17 . Artemisinin compounds can exert anticancer effects by inducing ferroptosis 18 . The underlying mechanisms are associated with the regulation of iron metabolism, ferritin autophagy, oxidative stress and endoplasmic reticulum stress 19–22 .…”
Section: Discussionmentioning
confidence: 99%
“…System xc‐/GSH/glutathione peroxidase 4 (GPX4) axis plays a pivotal role in preventing lipid peroxidation induced ferroptosis 17 . Artemisinin compounds can exert anticancer effects by inducing ferroptosis 18 . The underlying mechanisms are associated with the regulation of iron metabolism, ferritin autophagy, oxidative stress and endoplasmic reticulum stress 19–22 .…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic pathway was driven by blocking the intracellular antioxidant enzymes (like glutathione peroxidase, GPX4) [ 14 ]. However, the extrinsic pathway involved the inhibition of the cell membrane transporters like the cystine/glutamate transporter (also called the system Xc − ) or by the activation of the iron transporters like lactotransferrin and serotransferrin [ 29 ]. Furthermore, a few earlier studies also reported that many clinical drugs could initiate ferroptosis by inhibiting system Xc − or GPX4 [ 30 32 ], providing a new way of treating cancer for oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, an iron-dependent, nonapoptotic form of regulated cell death that is independent of caspase activation, is often accompanied by the accumulation of reactive oxygen species (ROS) and lipid peroxides, a decrease in reduced glutathione (GSH) levels and the downregulation of glutathione peroxidase 4 (GPX4) [ 27 , 28 ]. Recent studies indicate that the peroxide bridge of ART could destroy the redox balance in tumor cells, resulting in oxidative stress and ROS accumulation [ 10 , 29 ]. Thus, we speculated that ROS-induced ferroptosis also occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Many drugs from natural products still have profound impacts on human beings [ 4 , 5 , 6 , 7 ]. Artemisinin (ART), an important naturally occurring endoperoxide-containing sesquiterpene lactone with excellent antimalarial activity, has also been proven to exhibit significant antitumor activity in recent research [ 8 , 9 , 10 ], and several successful structural modifications or hybrids of artemisinin have been reported [ 11 , 12 , 13 , 14 , 15 , 16 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%